The Control Society: Anti-Extremism and Social Control in and by the Army in Franco’s Spain - Martínez López, Diego (Hispania Nova, 2024)
Between 1968 and 1972, the Francoist state laid the structural foundations of a repressive framework focused on combating social subversion and political dissent, an effort in which military intelligence services played a prominent role. The origin of this struggle and the mechanisms used for its suppression are rooted in the Civil War and the reorganization of the Army carried out in the immediate post-war period, which led to the definition and implementation of a series of internal control instruments in military units that would have profound repercussions on civil society. This article offers the initial conclusions drawn from the systematic study of the Bulletins and information notes prepared by the Intelligence Services throughout the Franco´s rule, providing a new perspective on the social control mechanisms employed by the regime during its final years.